Pseudorivibacter rhizosphaerae gen. nov., sp. nov., isolated from rhizosphere soil of Camellia sinensis (L.) O. Ktze and emended description of the genus Rivibacter. Issue 2 (25th November 2019) - Zhou, Xing-Kui; Li, Qing-Qing; Dong, Li-Min; Yang, Deng-Qiang; Liu, Lan; Fang, Bao-Zhu; Jeon, Che Ok; Li, Wen-Jun; Duan, Yan-Qing
Abstract : A Gram-stain-negative, facultative anaerobic, motile and straight rod-shaped bacterium, designated strain C1-9 T, was isolated from rhizosphere soil of Camellia sinensis (L.) O. Ktze collected from a tea garden in Huize, south-western PR China. Cells were oxidase-positive and catalase-negative. Growth occurred at 20–40 °C and pH 6.0–10.0, with an optimal growth at 30 °C and pH 7.0. The respiratory quinone was detected as ubiquinone-8 (Q-8). The major fatty acids were identified as summed feature 3 (C16 : 1 ω7 c and/or C16 : 1 ω6 c ), C16 : 0 and summed feature 8 (C18 : 1 ω7 c or C18 : 1 ω6 c ). The cellular polar lipids contained phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, three unidentified phospholipids, two unidentified lipids, one unidentified aminophospholipid and one unidentified aminolipid. The polyamine types were detected as 1, 8-diaminooctane and 2-hydroxyputrescine. The genomic DNA G+C content was 68.6 mol%. Based on the results of 16S rRNA gene sequence analysis, strain C1-9 T (MF687442) showed highest sequence similarity to Rivibacter subsaxonicus DSM 19570 T (97.1 %). The phylogenetic tree based on 16S rRNA gene sequences showed that strain C1-9 T clustered close to R. subsaxonicus DSM 19570 T, Methylibium petroleiphilum CCTCC AB 2014193 T and species belonging to the genera Rhizobacter and Piscinibacter . The phylogenomic tree indicated that strain C1-9 T formed a clade with R. subsaxonicus . The average nucleotide identity value was 76.0 % between strain C1-9 T and R. subsaxonicus DSM 19570 T, which is lower than the prokaryotic species delineation threshold of 95.0–96.0 %. The polyphasic taxonomic characteristics indicated that strain C1-9 T represents a novel species of a new genus within the order Burkholderiales, for which the name Pseudorivibacter rhizosphaerae gen. nov., sp. nov. (type strain C1-9 T = KCTC 62325 T =CGMCC 1.13864 T ) is proposed.